Sociedad 5.0 como parte de una nueva cultura sustentable. - Carro Suárez, Jorge; Sarmiento Paredes, Susana (Andamios)
Society 5.0 is based on the principle that technology should not only promote industrial development, but also contribute to improving the quality of people’s lives. Thus, what is needed today are principles that view technology as a critical component that not only generates overall societal well-being, but also allows us to address the major social, economic, and environmental problems that plague the world. Therefore, the aim of this research was to propose a set of principles for Society 5.0 to promote the development of today’s society through a sustainable culture. To this end, a systematic review of research works on Society 5.0 was carried out through a bibliometric analysis in the Science Direct database. The most relevant findings were compiled through a Theory, Context, Characteristics and Methodology (TCCM) framework. The results revealed that human and social well-being, care for the planet and the evolution towards sustainable cities are the basic principles that support the development of Society 5.0, promoting new digital technologies as a fundamental part of a culture focused on the development of comprehensive sustainability.